Removal of residual koh from palm oil based biodiesel using deep eutectic solvents - Shahbaz, K.; Mjalli, F.S.; Hashim, M.A.; AlNashef, I.M. (2011)
The Produced biodiesel through the alkali-catalyzed transesterification must be treated before utilization as an alternative fuel. Low content of catalyst is one of the important pointers needed for passing the EN 14214 and ASTM D6751 international biodiesel standards. In this work, potassium hydroxide (KOH) was selected as catalyst for the transesterification reaction. Two different salts namely; methyl triphenyl phosphunium bromide (MTPB) and choline chloride (ChCl) in combination with four different hydrogen bond donors namely; glycerol, ethylene glycol, 2,2,2-trifluoroacetamide and triethylen glycol were selected to synthesis eighteen deep eutectic solvents (DESs). These DESs were employed as solvents for the removal of residual KOH from palm oil based biodiesel. The results revealed that all tested DESs were able to reduce the content of KOH. The [ChCl:glycerol] DESs and [MTPB:glycerol] DESs proved to be capable of high KOH removal from palm oil-based biodiesel with an average removal efficiency of 98.59% and 97.57% respectively.